To Be One in Christ : Intercultural Formation and Ministry - Ortiz, Fernando A. (Book collections on Project MUSE., 2015)
The priests and pastoral ministers of our day increasingly reflects the multicultural, multi-ethnic, and multi-lingual nature of the church in the United States. For a variety of reasons, they come from diverse ethnic backgrounds and countries of origin. Seminaries and religious communities are welcoming international candidates with the vision that diversity strengthens the character and mission of the church. Yet this ecclesial diversity also comes with unique challenges. To Be One in Christ is a groundbreaking resource that delves into the questions raised by these complexities and provides an in-depth analysis from theological, sociological, psychological, cultural, and Protestant perspectives. Gerard McGlone and Fernando Ortiz are both nationally recognized experts on the integration of psychology and spirituality in priestly life. The book they have edited investigates issues, answer questions, and provide insights on the increasingly multicultural settings and programs affecting seminary and religious formation. The comprehensive resource will be welcome by vocation directors, seminary formators, clergy, religious, and seminarians.